2016
DOI: 10.1186/s12955-016-0462-2
|View full text |Cite
|
Sign up to set email alerts
|

Applying Rasch analysis to evaluate measurement equivalence of different administration formats of the Activity Limitation scale of the Cambridge Pulmonary Hypertension Outcome Review (CAMPHOR)

Abstract: BackgroundElectronic formats of patient-reported outcome (PRO) measures are now routinely used in clinical research studies. When changing from a validated paper and pen to electronic administration it is necessary to establish their equivalence. This study reports on the value of Rasch analysis in this process.MethodsThree groups of US pulmonary hypertension (PH) patients participated. The first completed an electronic version of the CAMPHOR Activity Limitation scale (e-sample) and this was compared with two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…5 These tools evaluate the patient's and the family's perceptions of the impact of the disease on their lives, and they have long been used for adults and children in various medical disciplines (eg, the evaluation of pain management, rheumatoid arthritis, and pulmonary hypertension). [6][7][8] Moreover, it was demonstrated that children as young as 5 years can self-report pain intensity when they use age-appropriate standardized instruments. 9,10 Given the importance of patient-reported outcome tools in measuring HRQOL and the dearth of literature regarding the effect of OSA treatment on QOL, our aim was to (1) evaluate the impact of the treatment of persistent OSA on QOL with these tools and (2) compare parent-and selfreported Pediatric Quality of Life Inventory (PedsQL) scores.…”
mentioning
confidence: 99%
“…5 These tools evaluate the patient's and the family's perceptions of the impact of the disease on their lives, and they have long been used for adults and children in various medical disciplines (eg, the evaluation of pain management, rheumatoid arthritis, and pulmonary hypertension). [6][7][8] Moreover, it was demonstrated that children as young as 5 years can self-report pain intensity when they use age-appropriate standardized instruments. 9,10 Given the importance of patient-reported outcome tools in measuring HRQOL and the dearth of literature regarding the effect of OSA treatment on QOL, our aim was to (1) evaluate the impact of the treatment of persistent OSA on QOL with these tools and (2) compare parent-and selfreported Pediatric Quality of Life Inventory (PedsQL) scores.…”
mentioning
confidence: 99%
“…Person and summary item fit residuals reflect perfect model fit if their mean and SD are close to 0 and 1, respectively 87 88…”
Section: Methodsmentioning
confidence: 99%
“…Mean scores can then be compared between groups. This is a fairly weak design to assess measurement equivalence [ 7 ]. In the latter design, participants are randomly assigned to one of two study arms in which they either first complete the P&P PRO and then the ePRO or the other way around.…”
Section: Introductionmentioning
confidence: 99%
“…The research designs, discussed above, assess only a small aspect of true measurement equivalence because they fail to address equivalence of item-level responses [ 7 , 8 ]. Contemporary approaches to measurement equivalence employ differential item functioning (DIF) analysis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation